COVID-19 patients display distinct SARS-CoV-2 specific T-cell responses according to disease severity - Marie Kroemer; Laurie Spehner; Lucie Vettoretti; Adeline Bouard; Guillaume Eberst; Sébastien Pili Floury; Gilles Capellier; Quentin Lepiller; Émeline Orillard; Laura Mansi; Anne‐Laure Clairet; Virginie Westeel; et al. (2020)
Adaptive Immune responses generated by SARS-CoV-2 virus in convalescent patients according to disease severity remain poorly characterized. To this end, we designed a prospective study (NCT04365322) that included 60 COVID-19 convalescent patients (1-month post infection) in two cohorts respectively entitled mild illness and severe pneumonia. The monitoring of peripheral immune responses was performed using IFNᵧ ELISpot assay. The serology index of each patient was investigated at the same time. Patients with severe pneumonia were older and had more comorbidities than patients with mild illness. T-cell responses in term of frequency and intensity were clearly distinct between mild illness and severe pneumonia patients. Furthermore, our results demonstrated that recent history of COVID-19 did not hamper viral memory T-cell pool against common viruses (Cytomegalovirus, Epstein-Barr-virus and Flu-virus). The presence of potent adaptive immunity even in patients who underwent severe pneumonia sustain the rationale for the development of protective therapeutics against SARS-CoV-2.